Efficacy of Nebulized Magnesium Sulphate in the Treatment of Acute Bronchial Asthma Compared to Nebulized Salbutamol: A Randomized Control Trial (Bangladesh Journal of Child Health, 2020)
Background: Nebulized salbutamol is commonly used in treatment of asthma in children. The use of nebulized MgSO4 is one of the different treatment options available during acute exacerbation.Objective: To compare the efficacy of nebulized MgSO4 with nebulized salbutamol in the treatment of acute asthma in children.Materials and method: This randomized controlled study was conducted in Dhaka Medical College Hospital between January to December 2016. Children of 7-12 years with acute exacerbation of asthma were randomized into study group-A (MgSO4 group, n=30) and control group-B (Salbutamol group, n=30). Children of both groups were treated with serial nebulization thrice at 20 minute intervals by either 2.4 ml (4% MgSO4, 96 mg) or salbutamol (0.15 mg/kg minimum 2.5 mg) with 2.5 ml of isotonic normal saline.Results: The mean final PEFR were not different between the two groups (275.0±41.42 L/min in MgS04 group and 263±36.17 L/min in salbutamol group). The increase in PEF was statistically significant and comparable in both groups (by 35.1% in the MgS04 group and by 42.1% in the salbutamol group). Fischl score improvement was comparable and significant in both groups (4.31 to 0.43 in MgS04 group and 4.29 to 0.76 in salbutamol group). Statistically significant increase in oxygen saturation and reduction of heart rate was found in MgS04 group without any side effects. Nebulized MgSO4 was found having significant bronchodilator effect which is comparable to salbutamol.Conclusion: Nebulized MgS04 was found equally effective as nebulized salbutamol in the treatment of severe acute asthma in children.Bangladesh J Child Health 2020; VOL 44 (1) :24-29